Gestión de planes internos y externos de emergencias en los hospitales de Medellín-2000 (2002)
ABSTRACT: A transversal study was made in order to know the state of emergency plans of the hospital in Medellin City. It included twenty one hospitals of first and second level of attention, and were requested about their antecedents of emergency, their antecedents with emergencies, coordination with the emergency net and the training programs. It was found that 71% of the institutions have committees, 86% have internal plans, 67% external plans and 14% do not have any plan. This situation must be taken into account, due to the lack of politics for the actualization of the plans, distribution of responsibilities, time for training and qualification, allocation of resources to mediate in the vulnerability. These results invite to promove the individual and collective commitment for the prevention and the attention of emergencies and disasters, to analyze the responsibility of professional in occupational health and administrators of hospital risks in the hospitals. The questions to be answered is: what to do to help hospitals administrators to have political, human and administrative vision for the prevention and attention in disasters, and at the same time give protection to patients, employees and visitors?"